2018
DOI: 10.18520/cs/v115/i3/534-540
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Conservation Status of Mangrove Communities in Two Areas of Mesocaribea Biogeographic Region

Abstract: The study of mangrove communities (Avicennia germinans, Conocarpus erectus, Laguncularia racemosa and Rhyzophora mangle) in Central America reveals a total diversity of 121 species included in 7 plant communities, of which 15 are characteristic of mangroves and 31 of flooded areas with less pronounced salinity, while 75 are invasive species belonging to neighbouring communities. Frequent fires in the dry forest have caused intense erosion, leading to the silting of the lake basin. As a result, the first belt o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…that the enrichment of the floristic assemblages can, in fact, be a sign of perturbation [13]. In Veracruz, the mangrove fringe is not continuous and is divided into smaller patches (<1000 ha) located between the coast and large coastal lagoons such as Tamiahua, Tampamachoco, and San Agustín [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…that the enrichment of the floristic assemblages can, in fact, be a sign of perturbation [13]. In Veracruz, the mangrove fringe is not continuous and is divided into smaller patches (<1000 ha) located between the coast and large coastal lagoons such as Tamiahua, Tampamachoco, and San Agustín [12].…”
Section: Methodsmentioning
confidence: 99%
“…Four mangrove species that vary in relative abundance dominate the structure of these forests: Rhizophora mangle L., Avicennia germinans (L.) L., Laguncularia racemosa (L.) Gaertn., and Conocarpus erectus L. [12]. It has been shown that well-preserved mangrove communities are composed, with local variations, of these mangrove species and that the enrichment of the floristic assemblages can, in fact, be a sign of perturbation [13]. In Veracruz, the mangrove fringe is not continuous and is divided into smaller patches (<1000 ha) located between the coast and large coastal lagoons such as Tamiahua, Tampamachoco, and San Agustín [12].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding biogeography, we have followed the work of Rivas-Martínez et al [7], which establishes three biogeographical provinces: Florida, Cuba and the Antilles, all part of the Caribbean-Mesoamerican Region. When studying the distribution of Melastomataceae in Central America and the distribution of 2050 endemic species on the island of Hispaniola, Cano et al [8][9][10] established the superprovince of the Western Antilles in which they include Cuba, Jamaica and the Florida peninsula. They maintain the biogeographical province of Florida with the sectors defined by Rivas-Martínez et al [7] and the province of Cuba with two subprovinces: the Cuban subprovince, with three biogeographic sectors (Eastern, Central and Western), and the Jamaican subprovince, with the Jamaican sector.…”
Section: Introductionmentioning
confidence: 99%
“…For the biogeographic study we have taken into consideration several factors, the geology of the territory, endemic species, distribution and origin of the flora, as well as the existing plant communities and their catenal contacts. [8][9][10] Solid knowledge about flora and vegetation provides a valuable basis for the implementation of biodiversity management and conservation measures [12][13][14]. The gaps of knowledge, both in native and alien species, are still today the subject of interest by numerous scholars around the world [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in alien plant invasion represents a very significant ecological problem for native flora [1]. This produces several impacts around the world such as the reduction of native and endemic species and habitats, but also damage to socio-economic and human health [2][3][4][5][6]. For example, R. pseudocacia L. has several effects on the endangered lichen species Lobaria pulmonaria (L.) Hoffm.…”
Section: Introductionmentioning
confidence: 99%